SCOTLAND’S INDEPENDENCE MOVEMENTS – THE MAIN CHALLENGES IN THE ECONOMIC SPHERE IN THE ASPECT OF POTENTIAL SEPARATION OF SCOTLAND FROM THE UNITED KINGDOM (EU and comparative law issues and challenges series (ECLIC), 2019)
The purpose of the article is to analyze the process of Scotland`s independence movements and to identify the main challenges in the economic sphere in the aspect of potential separation of Scotland from United Kingdom. As a basis for the research method a study based on the analysis of selected information sources was used. The attempts by Scotland to separation from the Great Britain, taken over the centuries, ended in failure, but have contributed to increase of Scottish autonomy. The results of the referendum on the United Kingdom’s continuing membership of the European Union have become the impulse for intensification of Scottish activity towards secession from the Great Britain. Scotland wants to decide independently on its own economic development based mainly on oil and natural gas as well as renewable energy sources. The EU membership would enable Scotland to attain the goals set up by Scottish government. The benefits of being a member of the EU, such as access to the Single European Market, structural funds, ect., Scotland may lose if it stays within the United Kingdom. The government in London is fully committed to maintaining the unity of the United Kingdom and blocks Scottish activities aimed at independence. Further scenario will depend on the results of the future directions, forms and principles for further co-operation between the United Kingdom and the European Union.